Using science and psychology to improve the dissemination and evaluation of scientific work - Buttliere, Brett T. (Frontiers in Computational Neuroscience, 2014)
Here we examine what science can tell us about the problems in psychological publishing and how to best address those problems. First, the motivation behind questionable research practices is examined (the desire to get ahead or, at least, not fall behind). Next, behavior modification strategies are discussed, pointing out that the carrot works better than the stick. Finally, we suggest that the best way to achieve real change is to make a tool so useful that academics make time to learn and utilize it on their own. Implementation of current change initiatives is hindered by a lack of norms, high initial buy-in costs, and uncertain payoffs. With this in mind, we pull together current open science tools to increase the utility while lowering effort and risk. One, centralized, easy to use, platform, with a profile, a feed of targeted science stories based on previous system interaction, a sophisticated (public) comment and rating section, and impact metrics which use the available data can be used to realign individual and group motives. Some advantages of centrally digitizing communications are outlined, including ways the data could be used to improve the peer review process.